Peripheries and urban segregation in Florianópolis: a state-of-the-art research based on the History discipline (PerCursos, 2023)
The present article aims to conduct a state-of-the-art review of the main academic works addressing urban periphery and urban segregation in Florianópolis, Santa Catarina. This is intended to introduce the material and themes relevant to the field of History. Drawing upon Valladares' surveys conducted in Rio de Janeiro in 2005, this article seeks to depict the primary topics, research methods, institutions, and knowledge areas observed in undergraduate theses, master's dissertations, and doctoral theses available in the repositories of major universities in Santa Catarina state and the country. A total of 46 works were analyzed, selected based on their relevance and approach to the selected themes: periphery, slums, urban segregation, and occupations in Florianópolis and its surrounding region. Through this analysis, I offer commentary on the relationship between the material and the historically situated reality in the city. I also discuss the potential for study and approaches for historians, primarily emphasizing interdisciplinary integration and the examination of cities and peripheries as subjects of study with their own dynamics, which have not yet been fully explored in the field of History.
Keywords: Florianópolis; periphery; urban segregation; state-of-the-art research